"Strategies for negotiating absent fathers among young people in Soweto, South Africa" - Mdletshe, Prudence (My University, 2014)
The family has been seen as playing an important part in children’s lives and their development. This is because families are seen to be the primary sources of individual development and thus should be seen as the building blocks of communities. Families serve as the main source of emotional, social and material support for most individuals. Thus, stable family environments are acknowledged to provide a fertile environment for children’s wellbeing and for them to grow up to be healthy responsible adults. Most South African children are raised by a single mother or by their maternal grandparents. Research conducted shows that South African Families face many challenges, and these challenges could be the source for high rates of absent fathers. Poverty has been identified to be one of the challenges that affect families in South Africa. Some researchers argue that poverty and inequality continue to undermine the family as an institution by reducing its effectiveness in realizing the roles of its members in society. Therefore poverty puts a burden on families and specifically on the main providers or ‘breadwinners’. Poverty in South Africa is mainly caused by lack of income, which is due to the high unemployment rates with little initiatives to reduce unemployment rates. The research was conducted qualitatively and specifically used narrative inquiry as a method of gathering data. In-depth, one-on-one narrative interviews were conducted in order to gain an in-depth understanding of the consequences of having an absent father and the strategies that young women adopted in order to deal with the consequences. Eight interviews with females aged from 18 – 21 years were conducted in Soweto. The findings reveal that the participants adopted both negative and positive coping strategies. Positive coping strategies include, creative writing, keeping a diary, maintaining a positive attitude, living a different life and speaking to others. Negative coping strategies included withdrawing from others, denial of a need of a father, self-blame, silence and defensive humor. More research is needed on how young people with absent fathers cope, paying into consideration issues of personality, culture and socialization.
Keywords: Absent; Fatherhood; Young women; Coping strategies; Distress; Soweto